A fundamentação da nulidade ontológica do mal no pensamento de Agostinho de Hipona - Lorenzetti, Darlan Paulo (2020)
The main objective of the present dissertation is to examine the process of grounding the ontological nullity of the evil undertaken by the Christian philosopher Augustine of Hippo (354430) in the context of patristic philosophy. In the first chapter, we reconstitute the general aspects of Augustinian cosmology, with emphasis on the concepts of: creatio ex nihilo (creation of nothingness), simultaneous creation, informal matter, rationes seminales (seminal reasons) and order. In the following chapter we seek to elucidate the foundations of the ontological notion of Good, taking the Augustinian concept of God and establishing a correlation between it and the idea of the Supreme Good. Next, we approach the concept of nature, trying at the same time to make a distinction between two levels, that is, divine nature and created nature, exploring the theme of the anthropological foundation of free will, qualifying it as a good. In the third and last chapter, we concentrate our attention on the presentation of the nucleus of Augustinian theodicy, that is, the thesis on the ontological nullity of evil and its definition as privatio (deprivation), in addition to exposing the categories of love and freedom of the will, as well as the hierarchy of created goods inherent in Augustine's ontology. Finally, we work on the concept of free will, placing and understanding evil from a moral perspective and, therefore, relative to human action, defining it as a consequence of the unregulated use of free will.